Human rabies in the United States: evaluation of clinical findings from 1960–2010 - Bass, J. M.; Petersen, B. W.; Mehal, J. M.; Blanton, J. D.; Rupprecht, C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Clinical diagnosis of human rabies is challenging in the United States (U.S.) due to the rarity of human cases, non-specific symptoms, and infrequent attainment of a potential exposure history. The traditional presentations of rabies, furious and paralytic, are reported in regions of endemic canine rabies, but have not been systematically characterized among rabies cases in the U.S. This study aims to examine the clinical characteristics of patients in the U.S. that are associated with rabies to aid in diagnosis and surveillance.